Assessment of Differential Item Functioning by School Ownership in 2020 WAEC SSCE Economics Multiple Choice Items - NKEKI, Jackson Joseph; ASEKOMHE, Theresa Ikhiaonotse (Ilorin Journal of Education, 2024)
The study aimed at assessing differential item functioning by school ownership in 2020 WAEC SSCE Economics multiple choice items. To achieve the objectives of this study, four research questions were raised and two hypotheses were tested. The Survey Research Design was adopted. Multi-stage Sampling Procedure was used to select the sample for the study. The population of the study comprised 41,830 students in SS3 in Benin metropolis who wrote the 2020 WAEC SSCE. The sample size for the study was four thousand one hundred and eighty-three (4,183) SS3 students. The research instrument used for the study was 2020 WAEC SSCE Economics multiple choice questions. Logistic Regression Analysis was used to detect DIF while the hypotheses were tested using Chi-Square Statistical Analysis. All hypotheses were tested at 0.05 level of significance. The findings showed that out of the fifty (50) items in WAEC 2020 Economics examination question paper, eight items function differentially by school ownership. From the results of the hypotheses of the 2020 WAEC SSCE Economics, the null hypotheses of no significant difference in the number of items functioning differentially by ownership was retained. Based on the findings, it was recommended that test experts and developers should explore the use of Logistic Regression Analysis to detect items with DIF.